Fabrication of (Bi0.5K0.5)TiO3 modified BaTiO3-Bi(Mg0.5Ti0.5)O3-BiFeO3 piezoelectric ceramics. Issue 7 (July 2021) - Khanal, Gopal Prasad; Fujii, Ichiro; Kim, Sangwook; Ueno, Shintaro; Wada, Satoshi
Abstract: The lead-free x (Bi0.5 K0.5 )TiO3 -0.23BaTiO3 -0.02Bi(Mg0.5 Ti0.5 )O3 -(0.75- x )BiFeO3 piezoelectric ceramics ( x = 0.05, 0.07, 0.09, and 0.11) were prepared by solid-state reaction method. The increase of (Bi0.5 K0.5 )TiO3 concentration revealed a decrease of dielectric maximum temperature ( T m ), however, the values were higher than 420 °C. The Rietveld structure refinement for each composition showed pseudo-cubic symmetry and the rhombohedral distortion (90 - α F ) was gradually decreased from 0.27° to 0.09° for x = 0.05 and 0.11, respectively. The saturation and remanent polarization were increased and a coercive field was decreased, while the critical exponent ( γ ) was increased from 1.407 ( x = 0.07) to 1.821 ( x = 0.11) revealing more relaxor-like behavior with higher (Bi0.5 K0.5 )TiO3 content. The remanent polarization, coercive field, and piezoelectric strain constant of 31.9 μC/cm 2, 23.6 kV/cm, and 315 pm/V, respectively, obtained in the composition with x = 0.11 are significantly higher than those reported previously for other Bi-based piezoelectric ceramics with T m >250 °C.